Breaking news how hardiness moderates the impact of burnout on the psychological well-being of Filipino journalists covering disasters and emergencies - Cerezo, Anna Gabrielle F.; Galian, Alison D.; Tarroja, Maria Caridad H.; Manalac, Gianina Kyla Q.; Ysmael, Ma. Patricia R. (2015)
The study examined the influence of hardiness on the impact of job
burnout and psychological well-being of 100 Filipino journalists
covering disasters such as wars, conflicts, natural disasters, accidents,
and other emergencies. Using multiple regression analysis, findings
reveal that hardiness buffers the effect of burnout on psychological well-
being. Implications of findings on future research and how journalists
can be prepared better to handle stress and burnout risks when covering
disasters are discussed.
Keywords: Disasters -- Psychological aspects; Disasters; Journalists